Double bass blues - Loney, Andrea J.; Gutierrez, Rudy (New York : Alfred A. Knopf, 2019)
After school orchestra practice, young Nic carries his double bass through rough neighborhoods to his grandfather's home, where he and Grandaddy Nic play jazz music with friends, delighting the neighbors.
Horn Book Starred, September 2019
Pub Weekly, August 2019
Kirkus Starred, August 2019
Booklist, September 2019
Bulletin (Center for Children's Books), October 2019
Caldecott Medal/Honor, 2020
Keywords: Double bass -- Juvenile fiction; Musicians -- Juvenile fiction; Bands (Music) -- Juvenile fiction; Grandfathers -- Juvenile fiction; Neighborhoods -- Juvenile fiction; African Americans -- Juvenile fiction; Double bass -- Fiction; Musicians -- Fiction; Bands (Music) -- Fiction; Grandfathers -- Fiction; Neighborhoods -- Fiction; African Americans -- Fiction